The level of representation of reading comprehension skills in the exercises of the Arabic My Language book for fifth grade pupils - an analytical study - Albases, Hatem Hussein (Al-Adab Journal, 2015)
This study aimed to recognize reading comprehension skills needed for grade five pupils from Basic Education, Also, to detect whether Reading Language Textbook Questions positively function for the reading comprehension skills suitable for it’s pupils.To achieve this aims, the researcher used the descriptive approach according to Content Analysis Method and a Standards of Reading Comprehension consists of five levels: literal, constructive, critical, appreciation, and creative comprehension incorporating (55) standards.The study results indicated that All the questions pertaining Arabic Language Textbook at intermediate level have been successful to cope with reading comprehension levels, in a relative weight (86.65%) from all reading exercises included in the textbook, but it was given some levels a high attention, the literal level at first in a relative weight (42.65%), constructive level in a relative weight (29.15%), critical level in a relative weight (12.56%), appreciation level in a relative weight (9%), and finally, creative level in a relative weight (6.64%), and the results was shown omission some reading skills which not get any chance for training